Development of Alternatives to Mitigate Deterioration of Segara Anakan Lagoon as Revealed by Analytical Hierarchy Process - Harnita Rosalina (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2016)
Segara Anakan is a lagoon located in estuary area of Citanduy and Cibeureum rivers. The main problem that exists in the region Segara Anakan is a shrinking area of Segara Anakan lead lagoon function becomes ineffective due to the increased volume of sediment in estuaries Citanduy. Refinement Segara Anakan will impact annual floods that occurred in the area downstream Citanduy. Have far-reaching is the decline in fish production, which makes the source of livelihood for the community residents of Kampung Laut, furthermore, the environmental changes that occurred in the area Segara Anakan have resulted in shrinking coastal fisheries resources and the expansion of land arising from silting. Assessment of the problem conducted by the method of approach of Analytical Hierarchy Process(AHP) to obtain the best alternatives among three alternatives being offered to sustain the function of Segara Anakan Lagoon. These three alternatives include the 1) Dredging the Lagoon and Upstream Watershed Conservation; 2) Dredging the Lagoon and Reclamation Work around Segara Anakan, and 3) Dredging the Lagoon and Citanduy Diversion. Some criteria and sub-criteria are adapted to support the selection of the alternatives and related questionnaires were developed, and the questionnaire filling was carried out through the implementation of Focus Group of Discussion or FGD. The criteria include several aspects of the criteria and sub-criteria are technical (floods, silting), socioeconomic (the tourist area, the local economy), as well as the environment (fisheries/shipping, agriculture and mangrove forests). Results of the analysis applying the AHP method showed the consistent value on the Alternative 3), i.e. the Dredging of the Lagoon and the Upstream Watershed Conservation (38%).